Hubungan Penggunaan Gadget dengan Kejadian Menarche pada Remaja - Cornelius Youwena; Hestya Galifatma; Nurul Fitriyah (Universitas Airlangga, 2023)
Background: Menarche is the occurrence of the first day of menstruation that is felt by every girl. Menarche generally occurs at the age of 12-15 years, but over time there has been a decline in age in the incidence of menarche. There are several factors such as the use of gadgets that have a major impact on the development of hormones in the body. Objectives: The purpose of this study was to determine how the relationship between the use of gadgets with the incidence of menarche in adolescent. Methods: This research method was descriptive with cross sectional design. This study used secondary data from the Indonesian Demographic and Health Survey 2017. The survey was conducted in 34 provinces of Indonesia from 24 July to 30 December 2017. The total sample was 10,678 respondents, all young girls aged 15-25 years according to the inclusive criteria (unmarried and menstruating). The variables used are the use of gadgets and the incidence of menarche in adolescents. The data analysis technique used is chi-square bivariate by displaying a frequency distribution table. Results: The results showed that the majority of respondents always use gadgets by 66.9%, the incidence of menarche in adolescent girls < 10 years (5.8%) and p-value <0.05 on the relationship between gadget use and the incidence of adolescent menarche. Conclusions: The conclusion of the study shows a relationship between the use of gadgets and the incidence of menarche, so it is necessary to give advice in this study, namely to socialize menarche and provide supervision to control the use of gadgets in adolescents.